Rethinking capacity utilization choice: The role of surrogate inventory and entry deterrence - Thomas I. Palley (Hans-Böckler-Stiftung, Macroeconomic Policy Institute (IMK), Forum for Macroeconomics and Macroeconomic Policies (FMM), 2021)
This paper presents a macroeconomics-friendly Post Keynesian model of the firm describing both an inventory theoretic approach and an entry deterrence approach to choice of excess capacity. The model explains why firms may rationally choose to have excess capacity. It also shows the two approaches are complementary and reinforcing of each other. Analytically, the paper makes three principal contributions. First, it provides a simple framework for understanding the microeconomics of capacity utilization choice. Second, it reframes the Post Keynesian discussion of capacity utilization by making excess capacity choice the key to understanding normal capacity utilization. Third, it implicitly challenges Neo-Kaleckian wage-led growth theory as the model shows choice of the optimal excess capacity rate is independent of the level of demand.
Keywords: D21; D24; E12; 330; Capacity utilization; excess capacity; surrogate inventory; entry deterrence; wage-led growth